THE APPLICATION OF DISCOVERY LEARNING MODEL TO IMPROVE STUDENTS' CHARACTER AND LEARNING OUTCOMES IN THEMATIC LEARNING IN CLASS IV OF DAYA 1 ELEMENTARY SCHOOL IN MAKASSAR CITY - Wa Santi; Rahmad Risan (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
This research presents the application of discovery learning model to improve students' character and learning outcomes in thematic learning in class IV of SD Negeri Daya 1 Makassar City. The purpose of this research is to describe the application of discovery learning model in thematic learning in class IV of SD Negri Daya 1 Makassar City, and to know the character of students after the application of discovery learning model in thematic learning in class IV of SD Negri Daya 1 Makassar City. The type of research used is class action research. The time and place of this class action research was conducted in the even semester of the 2023 school year in class IV of SD Negeri Daya 1 Makassar City. This research was conducted on Wednesday, January 12. The research subjects were teachers and students of class IV SD Negeri Daya 1 Makassar City which amounted to 23 people. The implementation procedure in this research is through two cycles consisting of several stages, namely, 1) planning 2) implementation 3) observation, and 4) reflection. The instruments used in this study were teacher and student observation sheets, interviews, learning outcome tests, and documentation. The data analysis technique used is descriptive qualitative data analysis. The improvement of students' thematic learning outcomes can be seen in the first cycle of student learning outcomes completeness of 60.86% or a total of 14 students out of 23 students in class IV. B SD Negeri Daya 1 Makassar City can be said to be incomplete and needs to be improved. In cycle II, the completeness of student learning outcomes was 100% or a total of 23 students out of 23 students. This research can be concluded that the application of the discovery learning model can improve student learning outcomes.